Intellectual property of fruit and vegetable cultivars in Brazil (Research, Society and Development, 2022)
The study aimed to carry out a broad mapping of the protections of fruit and vegetable cultivars operative in the National System for the Protection of Cultivars (SNPC), linked to the Ministry of Agriculture, Livestock and Supply (MAPA), identifying the participation of the public and private sectors. The research, exploratory, was carried out on the CultivarWeb portal, with the protections grouped according to the nature of the institutions obtained and separated into type/species, sector and type of breeder of the cultivar. 250 titles of fruit cultivars were found, highlighting the crops of grape, apple and strawberry, and 191 titles of vegetable cultivars, where lettuce, tomato and melon stood out. There was a dominance of the private sector with 50.4% of protections for fruit cultivars and 58.6% for vegetable crops, followed by the public sector, with 36.0 and 30.4%, respectively. Embrapa was the company that stood out the most, with 18.6% of the protection titles for these crops, but a factor that drew attention was the foreign domain, with 14.1% of the registrations, especially for fruit cultivars, where 60.4% of protections were from non-residents. The results indicate the need for Brazil, even with excellent climatic conditions and extensive territoriality of the country, to invest more in technology for the development and conservation of the fruit and vegetable chain, originating mainly from family farming, in order to meet both domestic and domestic demand, and increase participation in the foreign market.